2001
DOI: 10.1002/bsl.454
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between criminal charges, diagnoses, and psycholegal opinions among federal pretrial defendants

Abstract: This study analyzed data from 1710 criminal defendants referred by federal courts throughout the United States. We examined 12 categories of criminal charges with respect to diagnosed psychopathology and opinions related to competence to stand trial (CST) and criminal responsibility (CR) at the time of the alleged offense. Overall, 18% of the present sample were found to be incompetent to stand trial, while 12% were found to be not criminally responsible or 'insane.' In this study, crimes were associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
89
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 25 publications
10
89
1
Order By: Relevance
“…However, Cox and Zapf () found that an even higher rate of incompetence was found in patients diagnosed with non ‐psychotic major disorders (e.g., major depressive disorder, bipolar disorder). The latter finding was not confirmed by Cochrane, Grisso, and Frederick (), who found relatively low rates of incompetence in a sample of 1,719 federal criminal defendants evaluated for AC. The latter study, however, reported a relatively high rate of incompetence for AC examinees with organic diagnoses (38%) and those diagnosed with intellectual disability (30%).…”
Section: Empirical Correlates Of Ac Judgments and Psycholegal Abilitiesmentioning
confidence: 74%
See 1 more Smart Citation
“…However, Cox and Zapf () found that an even higher rate of incompetence was found in patients diagnosed with non ‐psychotic major disorders (e.g., major depressive disorder, bipolar disorder). The latter finding was not confirmed by Cochrane, Grisso, and Frederick (), who found relatively low rates of incompetence in a sample of 1,719 federal criminal defendants evaluated for AC. The latter study, however, reported a relatively high rate of incompetence for AC examinees with organic diagnoses (38%) and those diagnosed with intellectual disability (30%).…”
Section: Empirical Correlates Of Ac Judgments and Psycholegal Abilitiesmentioning
confidence: 74%
“…Cooper and Zapf (), Hubbard, Zapf, and Ronan (), and Warren et al () found that individuals charged with a violent crime were less likely to be deemed incompetent, while individuals judged incompetent were more likely to face charges for non‐violent offenses. Cochrane et al () found the highest rates of incompetence among individuals who were charged with offenses that would be considered serious and violent, but diagnosis rather than charges better explained AC findings. The authors cautioned that attempting to understand AC findings in relation to the severity of crimes may be misleading.…”
Section: Empirical Correlates Of Ac Judgments and Psycholegal Abilitiesmentioning
confidence: 99%
“…Some research also uses evaluator opinion as an outcome measure. Evaluators, on average, opine about 10% of referred defendants insane (Cochrane, Grisso, & Frederick, ; Johnson, Nicholson, & Service, ; Warren, Murrie, Chauhan, Dietz, & Morris, ; Warren, Rosenfeld, Fitch, & Hawk, ). Sometimes these opinions supportive of insanity focus on just one prong of the jurisdiction's insanity test.…”
Section: The Legal Backgroundmentioning
confidence: 99%
“…This phenomenon appears most likely to occur among individuals diagnosed with psychotic disorders, a group that is most likely to merit the insanity defense (Mossman et al, 2007). Indeed, individuals adjudicated not guilty by reason of insanity are most likely to have been diagnosed with a psychotic disorder (Cochrane, Grisso, & Frederick, 2001;Nestor & Haycock, 1997;Rogers & Shuman, 2000;Warren, Murrie, Chauhan, Dietz, & Morris, 2004).…”
Section: Abstract Forensic Evaluation Mental State At the Time Of Ofmentioning
confidence: 98%